Analisis Peran Orang Tua Terhadap Pendidikan Karakter Dan Akhlak Anak Di Dusun Rotonongo Desa Gerdu Kecamatan Karangpandan - Sufiyah Rahmawati; Martarosa Maulidia; Aisyah Nur Imani (Jurnal Budi Pekerti Agama Islam, 2024)
Character and moral education of children plays a crucial role in shaping a quality person. This research aims to analyze the role of parents in children's character and moral education in Rotonongo Hamlet, Gerdu, Karangpandan. This hamlet was chosen because its unique social and cultural context can provide in-depth insights into how the local environment influences children's character and moral development. A qualitative approach was used in data collection, through observations and interviews to understand parental behavior, values instilled, and character education strategies in the family environment. The results of the study are expected to provide a better understanding of the relationship between the role of parents and children's character education in Rotonongo Hamlet, as well as its implications for the development of effective character education programs that are appropriate to the local context. The conclusions of this study are expected to provide valuable contributions to efforts to improve the morality of the younger generation through the role of parents in the family environment.